ANALYSING THE EFFECTS OF DESTINATION IMAGE AND TOURIST SATISFACTION ON REVISIT INTENTION IN CASE BUNAKEN NATIONAL PARK - Samsudin, Atika (Jurnal Berkala Ilmiah Efisiensi, 2016)
Tourism plays a key role in the economic development of every countries in the world. Indonesia has a lot of tourism such as beaches, parks, gardens, heritage landscpe and anything in each Indonesia provincial. It will increase income, if tourists interests with the tourism themselves. Bunaken National Park is the national sea park in Indonesia to be objective destination for tourists. There are two factors to attract tourist revisit intention at Bunaken National Park which are destination image and tourist satisfaction. This reseacrh aims to analyze the effects of destination image and tourist satisfaction on revisit intention at Bunaken National Park. Multiple regression model is used to answer the research problem. The total sample for this research is 100 tourist who ever visitted Bunaken National Park. The obtain information had been using the questionnaire. The research findings showed that the independent variable destination image and tourist satisfaction has significantly effetcts to revisit intention. The government should give more attention about Bunaken destination image and its tourist satisfaction to be increase. It would made tourist to revisit intention and be loyal. It also increase the income of district, employment opportunity, and stakeholder attention.